Recycled 6xxx alloy sheet and its manufacturing method

By preparing 6xxx aluminum alloy plates with specific components and adopting specific manufacturing processes, the problems of composite aluminum alloy plate recycling and old waste treatment are solved, and efficient recycling of the plates and good molding adaptability, corrosion resistance and mechanical properties are achieved.

JP2025511154APending Publication Date: 2025-04-15CONSTELLIUM NEUF BRISACH SAS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024557974
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-02
Filing Date
2023-03-31
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively recover composite aluminum alloy plates, especially composite plates containing different alloys, and old waste products are difficult to recover, which is prone to pollution and performance degradation.

Method used

By preparing 6xxx aluminum alloy plates of specific components, including Si, Fe, Cu, Mn, Mg, Ti, Cr and other elements, vertical semi-continuous casting, hot rolling, cold rolling, dissolved heat treatment and natural aging, the good performance of the plates in recycling, molding and use are used.

Benefits of technology

It realizes efficient recycling and reuse of composite aluminum alloy plates, ensures the molding adaptability, corrosion resistance and mechanical properties of the plates, and is suitable for automotive body and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511154000001_ABST
    Figure 2025511154000001_ABST
Patent Text Reader

Abstract

The present invention is an aluminum alloy sheet having the composition: Si 1.25%-1.55%, Fe 0.60% or less, Cu 0.37% or less, Mn 0.22%-0.65%, Mg 0.25%-0.55%, Ti 0.15% or less, Cr 0.30% or less, Cr+Mn+Fe 0.90% or less, and Zn 0.15% or less. The alloy of the sheet allows recycling of the clad sheet in particular. The sheet has a good trade-off between contamination due to recycling and the properties of yield stress, formability and corrosion resistance both in T4 temper and after paint baking. The present invention is also a method for producing the sheet.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of aluminium alloy sheets for the stamping production of body-in-white parts for motor vehicles. [Background technology]

[0002] Aluminum alloys are increasingly being utilized in automotive construction to reduce vehicle weight and thereby reduce fuel consumption and greenhouse gas emissions.

[0003] There is also a need to reduce greenhouse gas emissions during the production of said alloys, which can be achieved by recycling scrap and waste aluminum alloys, thus reducing or even avoiding the use of primary aluminum produced by electrolysis and / or by the addition of additive elements.

[0004] The best electrolysis plants using hydroelectricity have a carbon footprint of 4 tonnes of CO2 equivalent (CO2eq) per tonne of cast plate, taking into account the use of carbon anodes. The typical carbon footprint of 1 tonne of electrolytic aluminium cast plate produced in Europe is 7 tonnes of CO2eq. The carbon footprint of 1 tonne of cast plate obtained only from scrap and waste is 0.5 tCO2eq per cast plate. CO2eq emissions are the amount of carbon dioxide (CO2) emitted that would induce an accumulated radiative forcing over the next 100 years equal to the amount emitted from a single or multiple greenhouse gases (GHGs). CO2eq emissions are obtained by multiplying GHG emissions by their Global Warming Potential (GWP) over the next 100 years. For a GHG mixture, the CO2eq emissions are obtained by adding the CO2eq emissions of each gas. If a plate is smelted partly using alloys from recycling, the CO2 equivalent of this plate is evaluated by linear interpolation between the electrolytic plate mentioned above (0% recycled) and a plate obtained only from scrap and waste (100% recycled). The recycling or recycling rate is the ratio between the weight of scrap and waste aluminium alloy used to smelt the plate and the weight of the plate, the remainder of the alloy being primary aluminium and / or added elements.

[0005] Simple recycling consists of recycling in a closed loop, i.e. scrap and waste aluminum alloys are recycled to obtain the same alloys that were once used to produce them. However, there are products that cannot be recycled in this way. This is in particular the case of clad sheets as defined in EN12258-1 (2012), §2.6.26, especially when they contain very different alloys. Clad sheets for the production of brazed heat exchangers fall into this case, since they generally consist of a core made of 3xxx series alloys, sometimes with small amounts of Cu and / or Mg, with one or more claddings of 4xxx series and / or 7xxx series and / or 1xxx series and / or 3xxx series alloys. Currently, these clad sheets are recycled rather in cast parts, where 4xxx series alloys are usually used. However, the shift from internal combustion propulsion to electric propulsion will destabilize this recycling sector. Aluminum alloy sheets in vehicles, specifically for body and structural parts, are in the prior art made of 5xxx and 6xxx alloys, which, taking into account their composition, are not suitable for the large-scale recycling of 4xxx series alloys. The evolution of alloys through research and development also makes it difficult to recycle old scrap, that is scrap coming from post-consumer products according to EN12258-1. This is the case for old scrap coming from the demolition of buildings, with a typical composition of 0.5% Si, 0.2% Fe, 0.1% Cu, 0.1% Mn, 0.1% Mg.

[0006] US Patent Application Publication No. 2021 / 0108293 discloses an aluminum alloy sheet having a chemical composition including 2.3-3.8% by weight Si, 0.35-1.05% by weight Mn, 0.35-0.65% by weight Mg, 0.01-0.45% by weight Fe, and at least one element selected from the group consisting of 0.0010-1.0% by weight Cu, 0.0010-0.10% by weight Cr, 0.0010-0.50% by weight Zn, and 0.0050-0.20% by weight Ti. The ratio of the Si content to the Mn content is 2.5 or more and 9.0 or less. The aluminum alloy sheet exhibits an elongation of 23% or more at a nominal strain of 3% and a strain hardening exponent of 0.28 or more. Such an aluminum alloy sheet is well suited for press forming (press processing) applications such as forming of automobile body panels.

[0007] WO 2018 / 175876 discloses a technique for casting metal products with high resistance and high formability from recycled waste metals without the addition of significant or even moderate amounts of primary aluminum. Supplementary alloying elements such as magnesium can be added to the waste metals, which can be cast and processed to produce metal coils of desired final thickness with desired metallurgical and mechanical properties such as high resistance and formability. In this way, cheap recycled waste metals can be effectively reused for new applications such as raw materials for automobiles or beverage cans.

[0008] The problem to be solved in JP 2005-298922 A is to provide an aluminum alloy sheet for forming at low cost, which has good hem bending workability, little bending anisotropy, excellent paint bake hardenability, little change over time at room temperature, and good ridging mark resistance. 1 / 10 , C 1 / 4 and C 1 / 2 is defined as the cube orientation density at each position of 1 / 10, 1 / 4, and 1 / 2 depth from the plate surface in the plate thickness direction, (C 1 / 10 +C 1 / 4 ) / 2>C1 / 2 and 30<(C 1 / 10 +C 1 / 4 )<500 and the {001} in the thickness direction in the region of 1 / 10 to 1 / 4 of the thickness <210> This is an aluminum alloy plate with an orientation density in the range of 2 to 50 and a 0°, 90° earing rate of 5% or more. The manufacturing method includes strictly specified casting conditions and hot rolling conditions. The structural conditions of the cast slab as an intermediate product and the structural conditions after hot rolling are specified.

[0009] WO 2022 / 026825 discloses a new 6xxx aluminum alloy. In one approach, the new 6xxx aluminum alloy can contain 0.25-0.60 wt% Fe, 0.8-1.2 wt% Si, 0.35-1.1 wt% Mg, 0.05-0.8 wt% Mn, up to 0.30 wt% Cu, up to 0.35 wt% Zn, up to 0.15 wt% Ti, up to 0.15 wt% each of Cr, Zr and V, with the remainder being aluminum, incidental elements and impurities. The new 6xxx aluminum alloy can be produced from recycled aluminum alloys.

[0010] Therefore, there is a need to recycle clad sheet scrap and waste to produce body sheets for the automotive industry. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] US Patent Application Publication No. 2021 / 0108293 [Patent Document 2] International Publication No. 2018 / 175876 [Patent Document 3] JP 2005-298922 A [Patent Document 4] International Publication No. 2022 / 026825 Summary of the Invention [Problem to be solved by the invention]

[0012] The problem to be solved is to develop a 6xxx series alloy sheet that aims for a good trade-off between: Recycling of scrap and waste, preferably of clad sheets. Clad sheets are generally made up of very different alloys, for example alloys of the 3xxx series for the central part, cladding alloys of the 4xxx series and / or 7xxx series. The average composition of clad sheets does not correspond to known alloys, making them difficult to recycle into other sheets. Moreover, in particular in the case of old scrap originating from post-consumer products, the recycling activity is inseparable from contamination phenomena that arise from mixing with other materials, for example steel, and that may reduce the properties of the material obtained after recycling. · Formability of the sheet assessed in T4 temper after natural ageing, which corresponds to the duration of transportation and storage between quenching of the sheet and its pressing into the form of the part. Formability is characterized using the LDH (Limiting Deformation Height) test for the ability to deform, and the yield stress for the stress that must be applied to obtain said deformation. Properties necessary for the use of parts in automobiles, evaluated on the final product and therefore after pressing, painting and paint baking of the sheets. Paint baking is also known to the skilled person as "bake hardening", since it may simultaneously cause hardening by ageing of the pressed sheets to obtain the properties necessary for the use of the parts in automobiles. Suitability for use in automobiles is characterized here by a deformation of 2% and by the yield stress of the sheets after a heat treatment of 170 °C for 20 minutes, representative of the heat treatment of the paint baking. Industrially, the paint baking may last for 10 to 30 minutes at temperatures of 170 to 195 °C. Corrosion evaluated on sheets after natural ageing. Corrosion is evaluated by filiform corrosion test on sheets after heat treatment at 170°C for 20 minutes. [Means for solving the problem]

[0013] The subject of the present invention is, in % by weight: Si: about 1.25% to about 1.55%, Fe: approx. 0.60% or less, Cu: approx. 0.37% or less, Mn: about 0.22% to about 0.65%, Mg: about 0.25% to about 0.55%, Ti: approx. 0.15% or less, Cr: approx. 0.30% or less, Cr+Mn+Fe: approx. 0.90% or less, Zn: approx. 0.15% or less, Other elements: 0.05% or less each, 0.15% or less in total, The rest is Al, The aluminum alloy sheet has the following composition.

[0014] Another object of the invention is a method for producing a rolled sheet of an aluminum alloy according to the invention, comprising the steps of: a. smelting an alloy, preferably from scrap and waste material, preferably including clad sheet; b. casting the alloy into a plate, preferably by vertical semi-continuous casting; c. homogenizing the plate at a homogenization temperature preferably between 540°C and 580°C, preferably above 550°C; d. hot rolling the plate; e. cold rolling the hot rolled plate; f. solution treatment followed by quenching; g. Pre-aging at a pre-aging temperature of 60-100°C for 2-16 hours, preferably obtained by coiling, followed by cooling to ambient temperature; h. Natural aging step for 72 hours to 6 months; The method includes the following successive steps: [Brief description of the drawings]

[0015] [Figure 1] The LDH according to the recyclability is shown. [Diagram 2] The LDH response to contamination of Fe, Mn and Cr alloys is shown. [Diagram 3]The trade-off between LDH and yield stress in T4 temper is shown. [Figure 4] The trade-off between LDH and yield stress after simulated paint bake is shown. [Diagram 5] 4 shows the yield stress in T4 temper as a function of recyclability for sheets according to the invention. [Figure 6] 4 shows the yield stress after paint baking simulation as a function of recyclability for the sheet according to the invention. [Figure 7] The results of filiform corrosion as a function of Cu content are shown. [Figure 8] A tool for measuring LDH is shown. [Figure 9] It is shown that the sheet according to the invention allows recycling of the clad sheet. [Figure 10] Photographs showing examples of samples that exhibited roping, classified as classes 1, 2, and 3 (1 average to 3 excellent). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] All aluminum alloys discussed below are designated in accordance with the conventions and names defined by the Aluminum Association in its periodic publication, the Registration Record Series, unless otherwise stated. Compositions are expressed in weight percent unless otherwise stated. The expression 1.4Cu means that the copper content, expressed in weight percent, is 1.4%.

[0017] The metallurgical tempers in question are designated according to the European standard EN-515.

[0018] The static tensile mechanical properties, in other words the tensile strength Rm, the conventional yield stress at an elongation of 0.2% Rp0.2, the plastic elongation Ag% and the elongation at break A% are determined by tensile tests according to the NF EN ISO6892-1 standard, with the sampling and test directions defined by the EN485-1 standard.

[0019] The strain hardening coefficient n is evaluated according to the EN ISO 10275 standard.

[0020] The elastic modulus is measured according to the ASTM 1876 standard.

[0021] The Lankford anisotropy coefficient is measured according to the EN ISO 10113 standard.

[0022] The bending angle, called alpha norm, is determined by a three-point bending test according to the NF EN ISO 7438 standard and procedures VDA 238-100 and VDA 239-200, 2017 edition.

[0023] Unless otherwise stated, the definitions in the EN 12258 standard apply.

[0024] The parameter LDH is widely used to evaluate the pressing suitability of sheets. It has been the subject of many publications, in particular the publication by R. Thompson, "The LDH test to evaluate sheet metal formability - Final Report of the LDH Committee of the North American Deep Drawing Research Group", SAE conference, Detroit, 1993, SAE Paper No. 930815. Here, reference is made to pressing tests of blanks that are fixed at the periphery by a ring. The blank holding pressure is adjusted to avoid sliding in the ring. A blank with dimensions of 120 mm x 160 mm is stressed in a manner close to a plane deformation. The punch used is hemispherical. Figure 8 clearly shows the dimensions of the tool used to carry out this test. Lubrication between the punch and the sheet is provided by graphite grease. The descent speed of the punch is 50 mm / min. The so-called LDH value is the displacement value of the punch at break, i.e. the limiting depth of pressing. This actually corresponds to the average of three tests and provides a 95% confidence interval for a measurement of 0.2 mm.

[0025] The standard for measuring intergranular corrosion is ASTM-G110.

[0026] The standard for filiform corrosion is EN3665.

[0027] The roping is measured in the following way: strips with dimensions of approximately 270 mm (transverse direction) x 50 mm (rolling direction) are cut from the thin sheet. They are then subjected to a tensile prestressing of 15% perpendicular to the rolling direction, i.e. along the length of the strip. The strip is then subjected to the action of an abrasive paper of the P800 type, which reveals the roping. This roping is then assessed visually and expressed by a classification on a scale from 1 (major roping) to 3 (no roping at all). An example of roping corresponding to values ​​1 to 3 is shown in Figure 10.

[0028] The ambient temperature is any temperature between 5 and 35°C that is suitable for human operation. The ambient temperature can be 5°C, 6°C, 7°C, 8°C, 9°C, 10°C, 11°C, 12°C, 13°C, 14°C, 15°C, 16°C, 17°C, 18°C, 19°C, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C.

[0029] The term "about," when used in connection with a measurable numerical variable, refers to the listed value of the variable, as well as all values ​​of the variable that fall within the limits of experimental error of the listed value or within a limit of ±10 percent of the listed value, with the highest value being held.

[0030] Detailed Description The present invention is based on the Applicant's verification that with the right composition and manufacturing methods it is entirely possible to produce sheets from recycled clad sheets having acceptable pressability, good corrosion resistance and mechanical properties suitable for the production of automotive bodies.

[0031] A typical composition of the alloy according to the invention is (in weight percent): Si: 1.25% to about 1.55%, Fe: approx. 0.60% or less, Cu: approx. 0.37% or less, Mn:0.22%~about 0.65%, Mg: about 0.25% to about 0.55%, Ti: approx. 0.15% or less, Cr: approx. 0.30% or less, Cr+Mn+Fe: approx. 0.90% or less, Zn: approx. 0.15% or less, Other elements: 0.05% or less each, 0.15% or less in total, The rest is Al.

[0032] Therefore, the concentration ranges imposed on the constituent elements of this type of alloy are explained by the following reasons: Si: Silicon is the main alloying element in aluminum-magnesium-silicon alloys (AA6xxx family) to form, together with magnesium, the intermetallic compounds Mg2Si or Mg5Si6, which contribute to the structural hardening of the alloy. A high Si content favors recyclability, for example when considering the use for cladding certain sheets clad with alloys rich in Si, such as AA4343, AA4045, AA4004 and other alloys, whose Si content can reduce the melting point. In weight percent, Si is in excess compared to Mg. Suitably, the Si excess is a minimum of 0.70 weight percent, more preferably 0.80 weight percent, and preferably a maximum of 1.20 weight percent, more preferably 1.15 weight percent. The purpose of this excess is to improve the ductility required for forming the sheet, but in the field of the present invention, the Si content has little effect on the formability measured by LDH. The Si content is between 1.25% and about 1.55%. In one embodiment, the Si content is at most about 1.35%, preferably at most about 1.30%. This embodiment allows low yield stress values ​​in the T4 temper, which reduces the pressing stress. In one embodiment, the Si content is at least about 1.30%, preferably at least about 1.35%, preferably at most about 1.40%, preferably at most about 1.45% and / or at most about 1.50%. This embodiment allows high yield stress values ​​after paint baking.

[0033] In one embodiment, the Si content is at least 1.25% and at most about 1.30% or at most about 1.35% or at most about 1.40% or at most about 1.45% or at most about 1.50% or at most about 1.55%. In one embodiment, the Si content is at least about 1.30% and at most about 1.35% or at most about 1.40% or at most about 1.45% or at most about 1.50% or at most about 1.55%. In one embodiment, the Si content is at least about 1.35% and at most about 1.40% or at most about 1.45% or at most about 1.50% or at most about 1.55%. In one embodiment, the Si content is at least about 1.40% and at most about 1.45% or at most about 1.50% or at most about 1.55%. In one embodiment, the Si content is a minimum of about 1.45% and a maximum of about 1.50% or a maximum of about 1.55%. In one embodiment, the Si content is a minimum of about 1.50% and a maximum of about 1.55%.

[0034] Fe: Iron is generally considered an undesirable impurity. The presence of iron-containing intermetallic compounds is generally associated with a decrease in local formability. The maximum Fe content is about 0.60%, preferably about 0.50%, more preferably about 0.40%. A reduction in the Fe content can improve the formability measured by LDH. However, on the one hand, alloys with a very high purity in terms of Fe are expensive, and on the other hand, scrap and waste are naturally contaminated with Fe by mixing with steel. Therefore, preferably, the Fe content is a minimum of about 0.05%, preferably about 0.10%, more preferably about 0.15%, more preferably about 0.20%. The Fe content must also be controlled in combination with Mn and Cr, taking into account the maximum content of the contaminants Cr+Mn+Fe, i.e. a content of less than or equal to about 0.90%, in order to control the LDH of the sheet according to the invention.

[0035] In one embodiment, the Fe content is at least about 0.25% and at most about 0.30% or at most about 0.35% or at most about 0.40% or at most about 0.45% or at most about 0.50% or at most about 0.55% or at most about 0.60%. In one embodiment, the Fe content is at least about 0.30% and at most about 0.35% or at most about 0.40% or at most about 0.45% or at most about 0.50% or at most about 0.55% or at most about 0.60%. In one embodiment, the Fe content is at least about 0.35% and at most about 0.40% or at most about 0.45% or at most about 0.50% or at most about 0.55% or at most about 0.60%. In one embodiment, the Fe content is a minimum of about 0.40% and a maximum of about 0.45% or a maximum of about 0.50% or a maximum of about 0.55% or a maximum of about 0.60%. In one embodiment, the Fe content is a minimum of about 0.45% and a maximum of about 0.50% or a maximum of about 0.55% or a maximum of about 0.60%. In one embodiment, the Fe content is a minimum of about 0.50% and a maximum of about 0.55% or a maximum of about 0.60%. In one embodiment, the Fe content is a minimum of about 0.55% and a maximum of about 0.60%.

[0036] Cu: In the AA6000 family of alloys, copper is an element that participates in hardening precipitation, which is advantageous for increasing the yield stress after T4 temper and paint bake. However, Cu is known to reduce corrosion resistance. The Cu content is a maximum of about 0.37%, preferably about 0.32%, preferably about 0.27%, more preferably about 0.25% to ensure an acceptable level of filiform corrosion. Increasing the maximum Cu content makes it possible to improve the recyclability of clad sheets containing Cu, as disclosed, for example, in WO 02 / 40729. Increasing the Cu content also makes it possible to improve the formability, as characterized by the LDH test. This effect is advantageous since it allows the content of contaminants, in particular Mn, to be increased, since the Cu content improves the LDH and compensates for the resulting LDH reducing effect of these contaminants. Thus, in one embodiment, the Cu content is a minimum of about 0.20%. In another embodiment, the Cu content is a maximum value of about 0.20%. This embodiment is advantageous since it allows to avoid the addition of Cu, a metal more costly than aluminum, for the recycling of clad sheets that do not contain Cu, such as clad sheets with a central part made of AA3003, a reference alloy well known to those skilled in the art of clad sheets.

[0037] In one embodiment, the Cu content is a minimum of about 0.05% and a maximum of about 0.07% or a maximum of about 0.12% or a maximum of about 0.17% or a maximum of about 0.22% or a maximum of about 0.27% or a maximum of about 0.32% or a maximum of about 0.37%. In one embodiment, the Cu content is a minimum of about 0.07% and a maximum of about 0.12% or a maximum of about 0.17% or a maximum of about 0.22% or a maximum of about 0.27% or a maximum of about 0.32% or a maximum of about 0.37%. In one embodiment, the Cu content is a minimum of about 0.12% and a maximum of about 0.17% or a maximum of about 0.22% or a maximum of about 0.27% or a maximum of about 0.32% or a maximum of about 0.37%. In one embodiment, the Cu content is a minimum of about 0.17% and a maximum of about 0.22% or a maximum of about 0.27% or a maximum of about 0.32% or a maximum of about 0.37%. In one embodiment, the Cu content is a minimum of about 0.22% and a maximum of about 0.27% or a maximum of about 0.32% or a maximum of about 0.37%. In one embodiment, the Cu content is a minimum of about 0.27% and a maximum of about 0.32% or a maximum of about 0.37%. In one embodiment, the Cu content is a minimum of about 0.32% and a maximum of about 0.37%.

[0038] Mn: Manganese has a similar effect to iron due to its contribution to common intermetallic precipitates. By lowering the Mn content, the formability measured by LDH can be improved. By increasing the maximum Mn content, it is possible to improve the recyclability of the clad sheet scrap and waste. In particular, this allows to increase the recyclability of clad sheets containing alloys disclosed in WO 02 / 40729 or alloys with Mn such as AA3003. One trade-off is a Mn content of at least 0.22% and at most 0.65%, preferably about 0.60%, preferably 0.55%, and preferably the minimum Mn content is at least about 0.25%, preferably about 0.30%, preferably about 0.35%, preferably about 0.40%, preferably about 0.44%. The Mn content must also be controlled in combination with Fe and Cr, taking into account the maximum content of the contaminants Cr+Mn+Fe, i.e., a content of about 0.90%, in order to control the LDH of the sheet according to the invention. Mn may slightly reduce the yield stress in the T4 temper, but this is unrelated to the inventors, no doubt due to its contaminant effect.

[0039] In one embodiment, the Mn content is a minimum of about 0.22% and a maximum of about 0.25% or a maximum of about 0.30% or a maximum of about 0.35% or a maximum of about 0.40% or a maximum of about 0.45% or a maximum of about 0.50% or a maximum of about 0.55% or a maximum of about 0.60% or a maximum of about 0.65%. In one embodiment, the Mn content is a minimum of about 0.25% and a maximum of about 0.30% or a maximum of about 0.35% or a maximum of about 0.40% or a maximum of about 0.45% or a maximum of about 0.50% or a maximum of about 0.55% or a maximum of about 0.60% or a maximum of about 0.65%. In one embodiment, the Mn content is a minimum of about 0.30% and a maximum of about 0.35% or a maximum of about 0.40% or a maximum of about 0.45% or a maximum of about 0.50% or a maximum of about 0.55% or a maximum of about 0.60% or a maximum of about 0.65%. In one embodiment, the Mn content is a minimum of about 0.35% and a maximum of about 0.40% or a maximum of about 0.45% or a maximum of about 0.50% or a maximum of about 0.55% or a maximum of about 0.60% or a maximum of about 0.65%. In one embodiment, the Mn content is a minimum of about 0.40% and a maximum of about 0.45% or a maximum of about 0.50% or a maximum of about 0.55% or a maximum of about 0.60% or a maximum of about 0.65%. In one embodiment, the Mn content is a minimum of about 0.45% and a maximum of about 0.50% or a maximum of about 0.55% or a maximum of about 0.60% or a maximum of about 0.65%. In one embodiment, the Mn content is a minimum of about 0.50% and a maximum of about 0.55% or a maximum of about 0.60% or a maximum of about 0.65%. In one embodiment, the Mn content is a minimum of about 0.55% and a maximum of about 0.60% or a maximum of about 0.65%. In one embodiment, the Mn content is a minimum of about 0.60% and a maximum of about 0.65%.

[0040] Mg: In general, the mechanical property level of AA6xxx alloys increases with the content of magnesium in combination with silicon to form the intermetallic compounds Mg2Si or Mg5Si6, especially after paint annealing, which is beneficial for reducing sheet thickness and vehicle weight. Magnesium contributes to an increase in the yield stress in the T4 temper, which increases the pressing stress, as well as an increase in the yield stress after paint baking, which allows for weight reduction of the body parts. In particular, Mg amplifies the response to paint baking, which is the difference between the yield stress after paint baking and the yield stress in the T4 temper. Mg is included at about 0.25% to about 0.55%. In one embodiment, Mg is a minimum of about 0.30%, preferably about 0.35%, and / or a maximum of about 0.50%, preferably about 0.45%. By limiting the Mg content, it is possible to maintain a low yield stress in the T4 temper, which is advantageous for formability, since excessively high pressing stresses are avoided. In one embodiment, Mg is at a minimum of about 0.45%, preferably about 0.50%. The addition of Mg makes it possible to improve the response to paint baking and to obtain a higher yield stress after paint baking. Increasing the Mg content makes it possible to improve the recyclability, especially of clad sheets whose cladding contains Mg, such as for example AA4004, or whose central part contains Mg, such as for example certain alloys disclosed in French patent 2797454.

[0041] In one embodiment, the Mg content is at least about 0.25% and at most about 0.30% or at most about 0.35% or at most about 0.40% or at most about 0.45% or at most about 0.50% or at most about 0.55%. In one embodiment, the Mg content is at least about 0.30% and at most about 0.35% or at most about 0.40% or at most about 0.45% or at most about 0.50% or at most about 0.55%. In one embodiment, the Mg content is at least about 0.35% and at most about 0.40% or at most about 0.45% or at most about 0.50% or at most about 0.55%. In one embodiment, the Mg content is at least about 0.40% and at most about 0.45% or at most about 0.50% or at most about 0.55%. In one embodiment, the Mg content is a minimum of about 0.45% and a maximum of about 0.50% or a maximum of about 0.55%. In one embodiment, the Mg content is a minimum of about 0.50% and a maximum of about 0.55%.

[0042] Cr: Cr can be added to refine the grains and stabilize the structure. A lower Cr content allows to improve the formability measured by LDH due to its contamination effect. A higher content allows to improve the recyclability of the alloy according to the invention. In fact, scrap and waste can be contaminated by a mixture of steel and Cr. Cr is at a maximum of about 0.30%. The trade-off between formability and recyclability is Cr+M+Fe at a maximum of about 0.90%. In one embodiment, to improve formability, Cr is at a maximum of about 0.20%, preferably at about 0.15%, preferably at about 0.10%, and suitably at about 0.05%. In one embodiment, Cr is an impurity.

[0043] Ti: A maximum content of about 0.15%, preferably 0.10%, is required to avoid primary crystal formation conditions during vertical casting, which have a detrimental effect on the overall claimed properties. This element can promote solid solution hardening leading to the required mechanical property levels, and this element also has a beneficial effect on ductility and corrosion resistance in service. In one embodiment, the Ti content is a minimum of about 0.01%.

[0044] In one embodiment, the Ti content is at most about 0.05% or at most about 0.10% or at most about 0.15%. In one embodiment, the Ti content is at least about 0.01% and at most about 0.05% or at most about 0.10% or at most about 0.15%.

[0045] Zn: the content is at most about 0.15%. As Zn is an additive element in aluminum alloys, it is advantageous to receive it for the purpose of recycling aluminum scrap and waste, especially from end-of-life vehicles. Indeed, Zn is used in certain cladding alloys of certain clad sheets, in particular AA7072 with a cladding of 10% of the thickness. Another cladding alloy containing Zn is disclosed by WO 02 / 55256. Considering the Zn content of AA7072 or the alloys of the aforementioned application, this content does not limit the use of such clad sheets to produce the alloys according to the invention. However, Zn is notorious for creating sensitivity to corrosion. Thus, limiting the Zn content can improve the corrosion resistance. In a preferred embodiment, Zn is at most about 0.10%. In one embodiment, Zn is at most about 0.05%. In one embodiment, Zn is an impurity.

[0046] Other elements are typically impurities whose contents are kept below 0.05%, preferably strictly less than 0.05%, with the total being less than 0.15%, the balance being aluminium.

[0047] The contaminant content of Fe, Mn and Cr must be controlled. The term contaminant is used to indicate that these elements may possibly be present in the alloy according to the invention due to recycling. However, without being bound to one theory, the inventors confirm that the effect of these elements is not detrimental and may have an unexpected beneficial effect on the properties obtained in the claimed proportions. Increasing the contaminant content can increase the recyclability. Reducing the contaminant content can increase the LDH. Preferably, the trade-off is that the contaminant content is a minimum of about 0.64% to a maximum of about 0.90%. In one embodiment, the contaminant content is from about Cu+0.41% to about Cu+0.59%, preferably from about 0.45%+Cu to about 0.55%+Cu. This embodiment is advantageous because it allows maintaining high LDH values. In a more preferred embodiment, the contaminant content is greater than about 0.70%, which can increase recyclability for copper-containing clad sheet.

[0048] In one embodiment, the sheet according to the invention has an LDH of 26.0 mm or less. The LDH is measured on a sheet of 1 mm thickness in T4 temper. Limiting the LDH is a trade-off that allows to improve the recyclability of the sheet according to the invention. Limiting the LDH is a trade-off that allows to increase the amount of contaminants in the sheet according to the invention. Limiting the LDH is a trade-off that allows to increase the yield stress of the sheet according to the invention both in T4 temper and after paint baking. In one embodiment, the sheet according to the invention has an LDH of 24.0 mm or more, preferably 24.5 mm or more, more preferably 25.0 mm or more, more preferably 25.5 mm or more. Increasing the LDH value allows to improve the formability in press working.

[0049] In one embodiment, the sheet according to the invention has a minimum yield stress Rp0.2 in the T4 temper of 100 MPa, preferably 110 MPa, more preferably 115 MPa, and / or a maximum yield stress Rp0.2 in the T4 temper of 150 MPa, preferably 145 MPa, more preferably 140 MPa. If the yield stress in the T4 temper is too low, the yield stress after paint baking will be limited. If the yield stress in the T4 temper is too high, the pressing stress will increase. Limiting the maximum value of the yield stress in the T4 temper is a trade-off that can improve the formability as measured by LDH. In one subembodiment, the yield stress Rp0.2 in the T4 temper is at most 135 MPa. This subembodiment is a trade-off that can increase the recyclability.

[0050] In one embodiment, the sheet according to the invention has a minimum yield stress Rp0.2 after paint baking of 200 MPa, preferably 210 MPa, and / or a maximum yield stress Rp0.2 after paint baking of 250 MPa, preferably 240 MPa. Increasing the yield stress after paint baking is advantageous for reducing the thickness of the parts. In one subembodiment, the yield stress after paint baking is at most 220 MPa, preferably 215 MPa. This subembodiment is a trade-off that allows to increase the recyclability.

[0051] In a preferred embodiment, the sheet according to the invention has an excellent filiform corrosion resistance according to EN 3665, with an average of less than about 0.25 cm, after painting and paint baking. Painting includes all the operations known per se of surface treatment, electrophoresis and painting. Paint baking, also known by the term bake hardening, can be simulated by a treatment at 170° C. for 20 minutes.

[0052] The method for producing a sheet according to the invention preferably comprises casting a plate by vertical semi-continuous casting and subsequent homogenization of the plate.

[0053] The plates are cast with an alloy according to the composition described above. The alloy is preferably partially smelted with scrap and waste, preferably with clad sheets. These clad sheet scrap and waste can also be end products to be recycled (old scrap according to EN12258-1), where parts are made with clad sheets. This is advantageous since these end products generally also consist of parts of very different alloys, not necessarily all components being clad, for example alloys containing Zn and alloys of the 3xxx series, for example alloys of the 7xxx series or alloys disclosed, for example, in EP 1 446 511 A1. The clad sheet scrap and waste can be used directly or indirectly for the smelting of the alloy. Indirect use is advantageous when the clad sheet scrap and waste are coated with paint or varnish or when the clad sheet scrap and waste are equipped with plastic parts. In these cases, it is preferable to remelt them in specialized units known to those skilled in the art of recycling, which properly treat the coatings or plastic parts, for example by filtering the fumes, etc. Direct use is advantageous because it is simple and economical to organize, since it consists of putting scrap and waste materials directly into a melting furnace to smelt the alloys.

[0054] The recyclability is evaluated as follows: firstly, it is necessary to calculate, estimate or measure for each element the average composition, preferably of the scrap or waste of the clad sheet. Then, for each element, the percentage ratio of the maximum value of the alloy of the sheet according to the invention to the content of that element in the average composition of the scrap and waste of the clad sheet is calculated. The recyclability is the minimum value between all these ratios. This recyclability is therefore the maximum value of the scrap and waste of the clad sheet that can be added in the alloy of the sheet according to the invention, the alloy composition of the sheet according to the invention being obtained by the addition of primary aluminum and / or added elements.

[0055] Increasing recyclability allows to reduce the amount of CO2 equivalent released to cast the plate. Preferably, the plate is smelted with at least 10%, preferably at least 20%, preferably at least 30%, preferably at least 39%, preferably at least 46%, preferably at least 48% scrap and waste. In one embodiment, a recyclability of up to 45% is a trade-off that allows to improve the yield stress after T4 temper or paint bake.

[0056] The preferred dimensions of the plate according to the present invention are a thickness of 200 mm to 600 mm, a width of 1000 to 3000 mm, and a length of 2000 to 8000 mm.

[0057] The plate is typically homogenized at a homogenization temperature above the solvus temperature of the alloy while avoiding localized or incipient melting for a minimum of 2 hours, preferably 3 hours, more preferably 4 hours, and a maximum of 7 hours, preferably 6 hours, more preferably 5 hours. The homogenization temperature is preferably at most 580°C, preferably 570°C, more preferably 560°C, more preferably 555°C, and a minimum of 540°C, preferably 550°C. Excessively high or excessively low temperatures will degrade the mechanical properties of the sheet.

[0058] The plate is then transferred to a hot rolling mill. Optionally, the plate is transferred directly from homogenization to hot rolling, the temperature of which may naturally drop by 5-35° C. during this transfer. Optionally, the plate is cooled by forced cooling from the homogenization temperature to the hot rolling start temperature. This forced cooling is preferably carried out at a direct cooling rate of at least 150° C. per hour. Advantageously, the direct cooling rate is at most 500° C. per hour. The cooling can typically be carried out by a machine such as that described in WO 2016 / 012691. Advantageously, this cooling is carried out in two steps: spraying and homogenization. Optionally, this cooling can be carried out in two passes in a machine such as that described in WO 2016 / 012691.

[0059] The homogenized plate is then hot rolled to a thickness of typically 4 mm, preferably 3 mm to 8 mm. The starting temperature for hot rolling is typically 520-550°C. Optionally, the hot rolling temperature after cooling is 390°C-510°C or 490°C or 470°C or 450°C or 430°C or 410°C. Optionally, the hot rolling temperature after cooling is 410°C-510°C or 490°C or 470°C or 450°C or 430°C. Optionally, the hot rolling temperature after cooling is 430°C-510°C or 490°C or 470°C or 450°C. Optionally, the hot rolling temperature after cooling is 450°C-510°C or 490°C or 470°C. Optionally, the hot rolling temperature after cooling is 470°C to 510°C or 490°C. Optionally, the hot rolling temperature after cooling is 490°C to 510°C.

[0060] The temperature transition between the start and end of hot rolling is due to the equipment of the hot rolling mill, such as, but not limited to, the conveying cylinders or rollers, as well as the heating associated with the deformation energy and the cooling by normal heat exchange of the plates with air at the ambient temperature of the plant using normal cooling or lubricating fluids. Preferably, the end temperature of hot rolling is between 350°C and 450°C.

[0061] The hot rolled plate is then cold rolled into sheet, typically 0.7-1.5 mm thick. Between the two steps of cold rolling, an intermediate annealing can also be performed. The annealing can be carried out in a static or continuous furnace.

[0062] The sheet is then solution treated, while avoiding local or incipient melting, typically at a solution temperature above the solvus temperature of the alloy, and then quenched, preferably in a continuous furnace. Too low a solution treatment and / or too short a solution treatment will reduce the mechanical properties of the sheet due to insufficient solution treatment. Too high a solution treatment will induce incipient melting, reducing the mechanical properties. Too long a solution treatment will reduce productivity. Preferably, the solution treatment lasts from 15 seconds to 300 seconds. The solution treatment temperature is preferably a minimum of 530°C and a maximum of 570°C.

[0063] The sheet is then typically quenched with water or air at a rate of more than 30° C. / s and better at least 100° C. / s, or with a continuous combination of water or air. Preferably, the sheet is quenched to a temperature of 60-100° C. Insufficient cooling rates will result in incomplete subsequent solution treatment, resulting in reduced mechanical properties of the sheet.

[0064] The sheet is then heated to perform pre-aging at a pre-aging temperature between 60°C and 100°C for 2 to 16 hours. Heating is useful if, between quenching and pre-aging, the sheet undergoes a surface treatment at a temperature lower than the pre-aging. Pre-aging is preferably obtained by coiling and then cooling to ambient temperature, preferably for at least 40 hours. Pre-aging makes it possible to improve the response to paint baking, which is the difference between the yield stress in the T4 temper and the yield stress after the paint bake.

[0065] The pre-aged sheet is in T4 temper and then naturally aged at ambient temperature for a period between 72 hours and 6 months. This step is a constraint related to storage before forming. The sheet according to the invention is formable despite the natural ageing.

[0066] The sheet according to the invention is advantageously used for producing automotive body parts. In one embodiment, the sheet according to the invention is a sheet for linings, for example door or bonnet linings. For automotive parts, in particular for linings, the thickness is between 0.7 and 1.5 mm. A thickness below 0.7 mm is too thin to ensure the rigidity of the component including the lining. A thickness above 1.5 mm makes the component including the lining too heavy for the user and the vehicle. Since the lining is not a part visible from the outside of the vehicle, the surface condition of the lining sheet as delivered and after painting is not comparable to the external parts of the vehicle body. In one embodiment, the roping of the sheet according to the invention is at most 1.

[0067] [Example] The present disclosure is further illustrated by the following examples, which are intended to be illustrative only and not limiting of the present invention.

[0068] Plates of various compositions were cast according to the alloys in Table 1. Alloy A is a typical alloy of US Patent Application Publication No. 2021 / 0108293. Alloy B is a typical alloy produced to supply vehicle body sheets made of alloy AA6016. In Table 1, examples according to the invention are identified as E and counter-examples as CE.

[0069] [Table 1]

[0070] The recyclability was evaluated using clad sheets as disclosed by WO 02 / 40729 by selecting a cladding on each side of 10% of the core. For the purpose of recycling such sheets, the average composition of the clad sheets in the table below is calculated:

[0071] [Table 2]

[0072] The recyclability of the various alloys A-P is evaluated below by calculating for each element the maximum amount of the average composition calculated in table 2. A value above 100% means that the clad sheet does not provide the amount of the element considered and therefore there is nothing to limit the introduction of the clad sheet to produce the alloy for the element considered. A value below 100% means that the clad sheet provides an excess of the element considered and that the introduction of the clad sheet must be limited to produce the alloy. Therefore, for each alloy evaluated, it is only necessary to consider the minimum values ​​for all elements to define its recyclability. For Cr and Ti, the calculation of the recyclability is not performed using the Ti and Cr contents of the alloy under test, but using a value of 0.05%, which corresponds to the maximum value of the traditional impurities of 0.05%.

[0073] [Table 3]

[0074] Plates A-N were homogenized at a temperature of 555°C for 4 hours, then hot rolled to a thickness of 6 mm at a hot rolling start temperature of 550°C, and then cold rolled to sheets with a thickness of 1 mm. These sheets were then solution treated at a temperature above 530°C for 15 seconds and then quenched to a temperature of 60°C. The sheets were then pre-aged at 80°C for 16 hours.

[0075] Plates O and P were homogenized at 560°C for 2 hours and then cooled by forced cooling to the hot rolling start temperature of 400°C. The plates were hot rolled at a temperature of 305°C to a thickness of 3 mm. The plates were then cold rolled to a thickness of 1.2 mm, then solution treated at a PMT (peak metal temperature) of 560°C and then quenched. Then pre-aging was performed by heating to a temperature of 65°C, then coiled and then naturally cooled to ambient temperature.

[0076] The mechanical properties were tested in the T4 temper. The results are shown in Table 4. The last column is the yield stress of these samples after 7 days of natural aging after simulating a paint bake (bake hardening or BH) with a heat treatment of 170°C for 20 minutes. The TL direction is transverse to the rolling direction.

[0077] [Table 4]

[0078] Figure 1 shows that sheets K, L, M, N, O and P according to the invention are a good trade-off between formability and recyclability. In fact, sheet B has slightly better formability but very poor recyclability. The other sheets may have better recyclability but have significantly reduced formability.

[0079] Figure 2 shows that sheets K, L, M, N, O and P according to the invention are a good trade-off between formability and the level of contamination by Fe, Cr and Mn. In fact, sheet B is a high purity alloy with a slightly better formability but a lower content of contaminants. The other sheets contain higher contents of the contaminants Fe, Cr and Mn, but with a significantly reduced formability.

[0080] Figures 3 and 4 show the sheets that follow the trade-off between LDH (formability) and Rp0.2 (forming stress) in the T4 temper, and between LDH and Rp0.2 after simulated paint bake (BH or bake hardening). Sheets K, L, M, N, O and P show a better trade-off than the other sheets (except for Sheet B, which is not according to the invention due to its low Mn content, one of the contaminants). Sheets K and L have similar formability levels to Sheets M and N due to their Cu content, which compensates for the Mn+Cr+Fe contaminant levels.

[0081] Figure 5 shows two different favorable trade-offs between recyclability and yield stress after T4 temper and paint bake. Sheet N has better yield stress after T4 temper and paint bake, and slightly lower recyclability. Sheet L has better recyclability and slightly lower yield stress after T4 temper and paint bake.

[0082] Sheets K and L have better recyclability compared to sheets M and N due to their higher Mn content.

[0083] Sheet N allows to obtain the best yield stress after paint bake due to the increase in Mg compared to Sheet M, while maintaining the yield stress in T4 temper comparable to Sheet M due to the decrease in Si content. A Mn content of less than 0.50% makes it possible to compensate the hardening effect in T4 temper in order to maintain the LDH level.

[0084] Sheets A to P were subjected to a filiform corrosion test according to the EN 3665 standard. For this purpose, the samples were subjected to surface and paint treatments known to the person skilled in the art. The samples were then subjected to a heat treatment of paint baking at 170° C. for 20 minutes. The samples were then scratched in the long rolling direction (L) and in the long transverse direction (TL) perpendicular to the rolling direction. The results of the filiform corrosion test are shown in the table below.

[0085] [Table 5]

[0086] Only samples A, B, D, H, K, L, M, N, O and P, which have a copper content less than 0.37%, have corrosion resistance to filiform corrosion with an average length of less than 0.25 cm.

[0087] Sheets B, H, K, L, M, N, O and P were also characterized after 90 days of natural aging. The sheets remain almost insensitive to natural aging.

[0088]

Table 6

Claims

1. In weight percent, Si is 1.25% to about 1.55%; Fe is about 0.60% or less, Cu is about 0.37% or less; Mn is 0.22% to about 0.65%, Mg is about 0.25% to about 0.55%; Ti is about 0.15% or less, Cr is about 0.30% or less; Cr+Mn+Fe is about 0.90% or less; Zn is about 0.15% or less; Other elements are each 0.05% or less and 0.15% or less in total, The rest is Al. An aluminum alloy sheet having a composition as follows:

2. 2. The sheet according to claim 1, characterized in that Cu is less than or equal to about 0.32%, preferably less than or equal to about 0.27%, more preferably less than or equal to 0.25%.

3. 3. Sheet according to claim 1 or 2, characterized in that Mn is greater than or equal to about 0.30%, preferably greater than or equal to about 0.35%, preferably greater than or equal to about 0.40% and / or Mn is less than or equal to about 0.60%, preferably less than or equal to about 0.55%.

4. 4. Sheet according to any one of claims 1 to 3, characterized in that Mg is greater than or equal to about 0.30%, preferably greater than or equal to about 0.35%, and / or Mg is less than or equal to about 0.50%, preferably less than or equal to about 0.45%.

5. Sheet according to any one of claims 1 to 4, characterized in that Cr is less than or equal to about 0.15%, preferably less than or equal to about 0.10%, preferably less than or equal to about 0.05%.

6. 6. Sheet according to any one of claims 1 to 5, characterized in that Ti is less than or equal to about 0.10%, preferably Ti is less than or equal to about 0.05% or Ti is greater than or equal to about 0.01%.

7. 7. Sheet according to any one of the preceding claims, characterised in that Zn is less than or equal to about 0.10%, preferably Zn is less than or equal to about 0.05%.

8. 8. Sheet according to any one of claims 1 to 7, characterised in that Si is less than or equal to about 1.50% and / or greater than or equal to about 1.30%, preferably greater than or equal to about 1.35%, preferably greater than or equal to about 1.40%.

9. 9. A sheet according to any one of claims 1 to 8, characterized in that the sheet has an LDH of less than or equal to 26.0 mm and / or more than or equal to 24.0 mm, preferably more than or equal to 24.5 mm, preferably more than or equal to 25.0 mm, the LDH being measured on a sheet of 1 mm thickness in T4 temper.

10. 10. Sheet according to any one of claims 1 to 9, characterised in that the sheet has a minimum yield stress Rp0.2 in the T4 temper of 100 MPa, preferably 110 MPa, more preferably 115 MPa, and / or a maximum yield stress Rp0.2 in the T4 temper of 150 MPa, preferably 145 MPa, more preferably 140 MPa.

11. a. smelting an alloy, preferably from scrap and waste materials, preferably including clad sheet; b. Casting the alloy into a plate, preferably by semi-continuous vertical casting; c. homogenizing the plate at a homogenization temperature preferably between 540°C and 580°C, preferably between 550°C and 580°C; d. hot rolling the plate; e. cold rolling the hot rolled plate; f. Solution treatment followed by quenching; g. Pre-aging at a pre-aging temperature of 60-100° C. for 2-16 hours, preferably obtained by coiling, followed by cooling to ambient temperature; h. Natural aging for 72 hours to 6 months; A method for producing a sheet according to any one of claims 1 to 10, comprising the successive steps of:

Citation Information

Patent Citations

  • Aluminum alloy plate to be formed, and manufacturing method therefor

    JP2005298922A

  • Aluminum-alloy sheet

    US20210108293A1

  • Casting recycled aluminum scrap

    WO2018175876A1

  • New 6xxx aluminum alloys and methods for producing the same

    WO2022026825A1